Implementation of Spice Route History Material in History Learning in Grade X at SMK Negeri 1 Samarinda - Sri Rahmayanti; Siti Marfuah (Yupa: Historical Studies Journal, 2026)
This study examines the implementation of spice-route history material in history learning in Grade X at SMK Negeri 1 Samarinda. It aims to describe how the material is implemented within the Merdeka Curriculum, including the teaching strategies used and students’ responses to the integration of spice-route material in history learning. This study uses a descriptive qualitative method, with data collected through observation, interviews, and documentation. The findings show that spice-route material is presented in Chapter 2 and functions as introductory material before broader topics, such as Hindu-Buddhist influence in Indonesia, are discussed. In the planning stage, teachers prepare Learning Outcomes (CP), Learning Objective Flow (ATP), and Teaching Modules. The learning resources used by teachers and students include school textbooks, articles, and other internet sources. The main obstacles faced by teachers and students are the limited availability of learning resources and restricted time allocation.